2014
DOI: 10.1177/1359105314539527
|View full text |Cite
|
Sign up to set email alerts
|

Are parents more willing to vaccinate their children than themselves?

Abstract: Risk perception studies have focused on personal risks; yet many decisions are taken for others. Some studies have suggested that parents are especially sensitive to risks to their children. We compared 245 parents’ willingness to vaccinate their child versus themselves in nine hypothetical scenarios relating to influenza strains. Scenarios varied according to non-vaccination risk (low, medium and high) and ‘risk target’ (oneself, one’s child or, as a comparator, one’s elderly parent). Participants were more w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…This has been explained by professional accountability when medical professionals make decisions [18]. When the general population decide for a stranger or family member, the reasons are not clear [19][20][21]. Interestingly, discrepancies have been found between surrogate choices and predictions.…”
Section: How Do Surrogates Make Decisions?mentioning
confidence: 99%
“…This has been explained by professional accountability when medical professionals make decisions [18]. When the general population decide for a stranger or family member, the reasons are not clear [19][20][21]. Interestingly, discrepancies have been found between surrogate choices and predictions.…”
Section: How Do Surrogates Make Decisions?mentioning
confidence: 99%
“…In the interpersonal domain, decision-makers seem to be less risk averse when making hypothetical decisions for a friend than for themselves [23,25–27]. In the medical domain, physicians seem to be more risk averse when making hypothetical decisions for a patient as opposed to themselves, as do parents when making hypothetical decisions for their children [2831]. However, in the financial domain, the literature is rather contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps participants were more likely to choose the status quo for others rather than more likely to choose the safer option, out of fear of being accountable for interfering with the natural course of events for example. However, studies that made the treatment option the safe option and the status quo the risky option also found that participants favored the safe option for others (Zikmund-Fisher et al, 2006; Ubel et al, 2011; Petrova et al, 2016; Tang et al, 2016). This sheds light on the confound in the present study and suggests that the explanation we propose holds for cases where the risky option is either taking or refusing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this reduction in risk-taking is not exclusive to doctors. It has also been found when people from the general population make decisions for a hypothetical patient (Zikmund-Fisher et al, 2006; Oliver, 2013), a family member (Zikmund-Fisher et al, 2006; Petrova et al, 2016; Tang et al, 2016; Carroll et al, 2017) or a stranger (Batteux, unpublished). This has been interpreted as surrogates being more cautious when deciding for someone else (Oliver, 2013), as well as stemming from the need to justify one’s decisions (Zikmund-Fisher et al, 2006), in which case maximizing survival chances is easier to defend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation